Anggaran Sebagai Alat Pengendalian Kinerja Pada PT Asuransi Kredit Indonesia (Askrindo) Cabang Jember Periode 2014-2016 - Afifah, Ulfiana Zahraini; Puspitaningtyas, Zarah; Puspita, Yeni (e-Sospol, 2017)
Abstract Fine corporate performance is required by each company under State-Owned Enterprises, one of which is insurance company. The performance can be seen from scheme dimension as the benchmark of company’s success in achieving its purpose. This research is aimed at describing budget implementation as performance control tool in 2014-2016 period at Asuransi Kredit Indonesia of Jember branch. The budget scheme under investigation dealt with company’s profit report. The research method was descriptive qualitative in nature. Budget scheme as performance control could be scrutinized by three aspects, comprising creation, management, and evaluation. The research findings evinced that the budget implementation as performance control was properly executed as seen from the aspect of company’s scheme creation applying Spander and Log system or Launching, in which figures were determined by referring to the guide map issued by the head office and interdivision coordination. The management aspect of targeted profit in 2015 only sufficed 26% of initial target, yet in 2014 and 2016 the company could surpass the targets. Nevertheless, overall the gaps were still beneficial in as much as the gap between income and underwriting was bigger than those between underwriting and expense. The aspect of scheme evaluation was carried out on monthly basis by applying implementer system and the calculation of scheme variant analysis